The prevalence of malnutrition in patients with gastrointestinal malignant tumors - Szczepanik, Antoni M.; Walewska, Elżbieta; Ścisło, Lucyna; Kózka, Maria; Kłęk, Stanisław; Czupryna, Antoni; Kulig, Jan (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Malnutrition is the immanent part of gastrointestinal malignant diseases. The prevalence of malnutrition is as high as 30-50% of patients on hospital admission. Perioperative mortality and morbidity in malnourished patients is higher and the prognosis poorer. Therefore, the proper early identification of malnourished patients and appropriate treatment is of high importance. The aim of the study. The aim of the study was the comparison of the results of selected screening methods for malnutrition in patients with gastrointestinal malignancies. Material and methods. Four commonly used measures of nutritional status were selected: percent of body weight loss, serum albumin level, absolute lymphocyte count and body mass index. Files of 915 patients with gastric cancer, pancreatic cancer and colorectal cancer were analyzed in order to determine their nutritional status using the methods listed above. Results and conclusions. According to the percent of weight loss parameter, 41% of the entire group were malnourished, 46.7% of gastric cancer patients, 63.4% of pancreatic cancer patients and 32.7% of colorectal cancer patients. Similar results were observed for absolute lymphocyte count 42.3%, 41.7%, 40% and 43% respectively. Low albumin level was observed in 16.9% of all patients, 21% of gastric cancer, 16.3% of pancreatic cancer and 14.4% of colorectal cancer patients. Low BMI was observed only in 9.9% of the entire group. Albumin level and the percent of weight loss were statistically correlated while this correlation was not observed for lymphocyte count and percent of weight loss. Our results suggest that the appropriate screening test for malnutrition may be the weight loss during 3-6 months prior to hospital admission. After this parameter is positive, further nutritional investigation is recommended. BMI has limited xalue as the screening test for malnutrition. Nursing Topics 2010; 18 (4): 384-392